1982
DOI: 10.1159/000123287
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of Melatonin Pituitary Inhibition for Luteinizing Hormone-Releasing Hormone

Abstract: The pineal indole melatonin suppresses the neonatal rat luteinizing hormone (LH) and follicle-stimulating hormone (FSH) responses to LH-releasing hormone (LHRH), as shown in previous studies from this laboratory. We show in this study that the melatonin inhibition is a selective effect and is not due to general inhibition of pituitary function. The effects of the indole on the responses to thyrotropin-releasing hormone (TRH) and somatostatin (SRIF) and on basal pituitary hormone secretion were examined with ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
2

Year Published

1985
1985
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 22 publications
0
30
2
Order By: Relevance
“…Its mechanism and site of action are still uncertain. Most studies suggest that melatonin exerts its main effect on the pituitary or within the central nervous system, either by suppressing pituitary responses to GnRH (14,29) or by inhibiting pulsatile hypothalamic GnRH secretion (30). However, circulating melatonin could also have a direct effect on the gonads.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its mechanism and site of action are still uncertain. Most studies suggest that melatonin exerts its main effect on the pituitary or within the central nervous system, either by suppressing pituitary responses to GnRH (14,29) or by inhibiting pulsatile hypothalamic GnRH secretion (30). However, circulating melatonin could also have a direct effect on the gonads.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged darkness, which prolongs melatonin synthesis, suppresses gonadal function in several mammalian species (5-7). Recently, melatonin was reported to be involved in such human reproductive processes as puberty (8) and the menstrual cycle (9-11).It is generally thought that melatonin exerts its antigonadotropic effect mainly at the level of the brain and pituitary (12)(13)(14). However, exogenous melatonin was found to be concentrated in rat and cat ovaries (15), and specific melatonin receptors were reported (16) in hamster, rat, and human ovaries.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the rat, a high density of pituitary 2-[l25I]iodomeIatonin binding sites was reported in neonatal animals. In adult rats, however, pituitary 2-[l25I]iodomelatonin binding sites were drasti cally reduced suggesting that pineal melatonin action on the pituitary may be restricted to the neonatal period [10,13]. Conversely, a significant number of 2-[l25I]iodomelatonin binding sites were demonstrated in the ma ture chicken and quail testis and/or ovary [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The effect was observed in pituitary glands from female rats aged 5, 10 or 15 days, but not older rats. Further studies (Martin, McKellar & Klein, 1980) revealed a similar effect in vivo, and Martin & Sattler (1982) showed that the inhibitory effect of melatonin was selective in that the stimulated release of thyrotrophin and prolactin by thyrotrophin-releasing hormone or the inhibition of growth hormone (GH) by somatostatin was not affected by melatonin in their pituitary cell cultures. More recently, Lang, Aubert, Conne et al (1983) showed that suitably timed low-dose melatonin administration will inhibit or delay sexual maturation in male rats.…”
Section: Introductionmentioning
confidence: 84%